Regional gene therapy with 3D printed scaffolds to heal critical sized bone defects in a rat model. Issue 10 (11th June 2019) - Alluri, Ram; Song, Xuan; Bougioukli, Sofia; Pannell, William; Vakhshori, Venus; Sugiyama, Osamu; Tang, Amy; Park, Sang‐Hyun; Chen, Yong; Lieberman, Jay R.
Abstract: The objective of the present study was to assess the ability of transduced rat bone marrow cells (RBMCs) that overexpress BMP‐2 loaded on a three‐dimensionally (3D) printed scaffold to heal a critical sized rat femoral defect. Tricalcium phosphate (TCP) scaffolds were 3D printed to fit a critical sized rat femoral defect. The RBMCs were transduced with a lentiviral (LV) vector expressing BMP‐2 or GFP. The rats were randomized into the following treatment groups: (1) RBMC/LV‐BMP‐2 + TCP, (2) RBMC/LV‐GFP + TCP, (3) nontransduced RBMCs + TCP, (4) TCP scaffold alone. The animals were euthanized at 12 weeks and evaluated with plain radiographs, microcomputed tomography (micro‐CT), histology, histomorphometry, and biomechanically. Each LV‐BMP‐2 + TCP treated specimen demonstrated complete healing of the femoral defect on plain radiographs and micro‐CT. No femurs healed in the control groups. Micro‐CT demonstrated that LV‐BMP‐2 + TCP treated femoral defects formed 197% more bone volume compared to control groups ( p < 0.05). Histologic analysis demonstrated bone formation across the TCP scaffold, uniting the femoral defect on both ends in the LV‐BMP‐2 + TCP treated specimens. Biomechanical assessment demonstrated similar stiffness ( p = 0.863), but lower total energy to failure, peak torque, and peak displacement ( p < 0.001) of the femurs treated with LV‐BMP‐2 + TCP when compared to the contralateral control femur. Regional gene therapy induced overexpression of BMP‐2 via transduced RBMCs combined with an osteoconductive 3D printed TCP scaffold can heal a critically sized femoral defect in an animal model. The combination of regional gene therapy and 3D printed osteoconductive scaffolds has significant clinical potential to enhance bone regeneration.